PENGARUH MODERNISASI TERHADAP PENELANTARAN LANSIA PADA KELUARGA DI KELURAHAN PANIKI BAWAH KECAMATAN MAPANGET (UNIT PELAKSANA TEKNIS DINAS BALAI PENYANTUNAN SOSIAL LANJUT USIA TERLANTAR â€œSENJA CERAHâ€) - Tatontos, Frastika; Kandowangko, Nicolaas (Universitas Sam Ratulangi, 2019)
An increase in the number of elderly people is not only seen as success in health, but it is also a problem with family, society, and Government regarding the high number of life dependency that will cored with the burden The economy is borne by the productive population to support the elderly.Families living in modern times are mostly industrial humans. The family has a high daily mobility that prefer staying with the core family. The family has eliminated various characteristic functions that have served its members as well as the community. This increased activity resulted in several impacts among them. The abandonment of the elderly is not only through physical matters, but also attacks on emotional and financial psychological disorders.The cause of the elderly in the orphanage BPSLUT because of the modernization that looks very thick especially in the center of the cities, which is characterized by the many elderly who are in the living orphanage without the burden of the family. The increasing number of elderly trends is a phenomenon that must be accepted, and require adequate attention and handling from various parties.Culture in modern society has undergone a shift in customs, and norms are also shifting in groups and shifting characters. Families should give affection and care to the elderly as well as children to parents. In this reality the child has ignored and brought the parents to the orphanage. There are also families who intentionally let their parents live alone. So the elderly prefer to go to the orphanage in order to get a decent place to stay and can interact with other elderly people.Keywords: elderly, family, abandonmentÂ